1999
DOI: 10.1063/1.478021
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular bonding and vibrations of phenol⋅oxirane

Abstract: High-resolution ultraviolet spectroscopy of p -fluorostyrene-water: Evidence for a σ -type hydrogen-bonded dimerThe supersonically cooled hydrogen-bonded phenol•oxirane complex was studied using mass-and isomer-selective laser spectroscopic techniques. The S 1 ←S 0 vibronic spectrum was measured by mass-selective two-color resonant two-photon ionization. UV/UV-hole-burning experiments prove that the whole observed spectrum is due to only one isomer. High-resolution fluorescence emission spectra yielded five di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Quite recently Al-Rabaa et al (15) reported enantiodifferentiation in jet-cooled van der Waals complexes: (R)-(+)-and (S)-(−)-α-methyl-2-naphthalenemethanol solvated with (S)-(+)-chloro-1-propanol by using laser induced fluorescence spectroscopy and Sarfati et al (16) a successful enatiometric differentiation of saturated chiral alkanes dissolved in a chiral polypeptide liquid crystal, by deuterium NMR spectroscopy. Leutwyler and his collaborators examined the chirality of a few hydrogen-bonded oxirane complexes by laser spectroscopic techniques (17) or by ab initio calculations (18). Vardi (19) discussed the effect of intermolecular interactions on coherent tunneling racemization within the framework of a double minimum model like gauche; namely, he set up equations of motion which were nonlinear due to the difference between homochiral and heterochiral interactions and showed that the nonlinearity contributed much to the chiral stability.…”
Section: E Effects Of Intermolecular Interactions On the Dynamical Bmentioning
confidence: 99%
“…Quite recently Al-Rabaa et al (15) reported enantiodifferentiation in jet-cooled van der Waals complexes: (R)-(+)-and (S)-(−)-α-methyl-2-naphthalenemethanol solvated with (S)-(+)-chloro-1-propanol by using laser induced fluorescence spectroscopy and Sarfati et al (16) a successful enatiometric differentiation of saturated chiral alkanes dissolved in a chiral polypeptide liquid crystal, by deuterium NMR spectroscopy. Leutwyler and his collaborators examined the chirality of a few hydrogen-bonded oxirane complexes by laser spectroscopic techniques (17) or by ab initio calculations (18). Vardi (19) discussed the effect of intermolecular interactions on coherent tunneling racemization within the framework of a double minimum model like gauche; namely, he set up equations of motion which were nonlinear due to the difference between homochiral and heterochiral interactions and showed that the nonlinearity contributed much to the chiral stability.…”
Section: E Effects Of Intermolecular Interactions On the Dynamical Bmentioning
confidence: 99%
“…Oxiranes have been recognized previously as being well suited in this context. 13,14,18 The availability of two complementary functional groups in each monomer helps to reduce the dimer Ñexibility and can be expected to enhance the chiral recognition e †ect.10 Glycidol 2,3-epoxypropan-1-ol, (C 3 H 6 O 2 , oxiranemethanol), a cyclic ether with an additional alcohol functionality, fulÐlls these requirements. While it also has two torsional degrees of freedom, two of the monomer conformations are strongly favored over the others due to the formation of a weak internal hydrogen bond.…”
mentioning
confidence: 99%
“…Némec et al [10] have defined the rCH 3 vibration from 1133 to 1136 cm 21 by FT-IR and at 1132 cm 21 by FT-Raman. Inauen et al [23] described the vibration frequencies of phenol-oxirane at 1112 cm 21 , the (1 þ 3t) at 1167 cm 21 and the (1 þ d) at 1176 cm 21 from fluorescence emersion spectra.…”
Section: Band Assignmentmentioning
confidence: 99%